Sexual behaviors, cannabis, alcohol and monkeypox infection - Vallée, Alexandre (Frontiers in Public Health, 2023)
The emergence of the monkeypox virus (MPXV) outbreak in 2022 is a worldwide health issue. The rapid increase of monkeypox cases caused the WHO to designate the escalating global monkeypox outbreak a Public Health Emergency of International Concern on July 23, 2022. The WHO has called on the group currently most affected by the virus, men who have sex with men (MSM), to limit their sexual partners. The diminution in number of sexual partners not only decreases the proportion of infected MSM but could also increases the number of days needed to reach a given infection level among the general population. Several behavioral factors could be associated with high levels of different sexual partners, such as cannabis use and alcohol consumption. Firstly, this review focuses on the association between cannabis and alcohol consumption and the number of sexual partners, and their possible impact on the current MPXV outbreak by impairing the immune responses. Secondly, this review investigated in the UK Biobank cohort the relationship between alcohol and cannabis use and the number of sexual partners. Among the 115,604 participants, 1.8% declared to be MSM, 1.9% to be WSW (women having sex with women), 43.3% men heterosexuals and 53.0% women heterosexuals. MSM and WSW showed higher lifetime sexual partners (N = 17.4 (SD:17.52) and N = 13.65 (SD: 13.21), respectively) compared to heterosexual men (N = 6.89 (SD: 9.47) and women (N = 5.19 (SD:6.56), p < 0.001. After adjustment for age, body mass index, lifetime sexual activity, educational and income levels, tobacco and cardiovascular diseases, cannabis use and alcohol consumption remained significantly associated with increase in the number of different sexual partners in all four subgroups. Thus, cannabis use and alcohol consumption may have two detrimental effects on the MPXV outbreak: by participating in the increase of the number of sexual partners which are mainly responsible for the augmentation of the number of new MPXV infected cases and by impairing the immune response to a viral infection. Health and safety policies should address the factors and practices, including chemsex, leading to an increase in risk of sexual behaviors responsible for MPXV dissemination in the worldwide population.